Association between Employer Provided and Planned Maternity Leave Duration and Breastfeeding Duration - Kamat, Natasha; Miller, Emily (Journal of Maternal and Child Health, 2022)
Background: The American Academy of Pediatrics recommends breastfeeding for at least one year. However, studies have shown that the constraints of the Family and Medical Leave Act (FMLA), which provides 12 weeks of unpaid leave, may impede this recommendation. Our objective was to evaluate whether employer provided and planned maternity leave duration was associated with breastfeeding duration. Subjects and Method: This was a prospective cohort study wherein 480 postpartum women were recruited from Prentice Hospital between May and July of 2017. Participants completed a questionnaire immediately postpartum and at 12 to 14 weeks postpartum. Independent variables were employer provided and planed maternity duration and partner leave duration. Dependent variables were intention to breastfeed for one year and actual breastfeeding status at 12 to 14 weeks postpartum. Bivariable and multivariable analyses were performed. Results: Of the 480 women enrolled, 226 (47.28%) intended to breastfeed for at least one year. Women who planned a longer maternity leave were significantly more likely to intend to breastfeed for at least one year (37.41% vs 35.71%, p= 0.033). This persisted after controlling for possible confounders (aOR = 4.08, CI 95%= 1.10 to 15.13, p= 0.040) However, there was no difference in intention to breastfeed for at least one year by the duration of employer allocated maternity or partner leave. There were no differences in actual breastfeeding rates at 12 weeks postpartum across various durations of intended or taken maternity or partner leave. Conclusion: Increased planned maternity leave duration is associated with increased intention to breastfeed, however actual breastfeeding rates at 12 weeks postpartum were not associated with maternity leave duration.